Strategic Petroleum Reserve. (U.S. Congressional Research., 2001)
Discusses rationale behind the Strategic Petroleum Reserve (SPR), and examines issues facing Congress, including establishment of regional home heating oil reserve, crude oil purchases, royalty-in-kind acquisition for the SPR, and drawdown of the reserve. Includes chronology.